Basal Insulin Initiation and Maintenance in Adults with Type 2 Diabetes Mellitus in the United States - Kalirai S (Dove Medical Press, 2020)
Samaneh Kalirai,1 Jasmina I Ivanova,2 Magaly Perez-Nieves,1 Judith J Stephenson,3 Irene Hadjiyianni,1 Michael Grabner,3 Roy Daniel Pollom,1 Caroline Geremakis,3 Beverly L Reed,1 Lawrence Fisher4 1Eli Lilly and Company, Indianapolis, IN, USA; 2Analysis Group Inc., New York, NY, USA; 3HealthCore Inc., Wilmington, DE, USA; 4Department of Family and Community Medicine, UC San Francisco, San Francisco, CA, USACorrespondence: Michael GrabnerHealthCore, Inc., 123 Justison St, Suite 200, Wilmington, DE 19801, USATel +1 302 230-2000Email mgrabner@healthcore.comObjective: A survey of US adults with type 2 diabetes mellitus was conducted to better understand patients’ insulin initiation experiences and treatment persistence behaviors.Research Design and Methods: Participants were recruited from consumer panels and grouped by basal insulin treatment pattern: continuers (no gap of ≥ 7 days within 6 months of initiation); interrupters (gap ≥ 7 days, resumed treatment); discontinuers (stopped for ≥ 7 days, not resumed). A quota of approximately 50 respondents per persistence category was set.Results: A total of 154 respondents (52 continuers, 52 interrupters, 50 discontinuers) completed the survey. Mean age was 51.4 years; 51.9% male. Continuers were more likely to report their views being considered during initiation, and less likely to report a sense of failure. Concerns included insulin dependence (64.3% agree/strongly agree), frequent blood glucose monitoring (55.2%), costs/ability to pay (53.9%), fears of or mistakes during self-injection (52.6%), and weight gain (52.6%). Continuers were motivated by benefits of insulin therapy; experienced or potential side effects were notable factors for interruption/discontinuation. Healthcare provider instruction was indicated as a reason for continuing, stopping, and restarting therapy.Conclusion: Benefits of basal insulin therapy motivated continuers while side effects impacted interruption/discontinuation. Persistence on basal insulin is often influenced by provider actions. Earlier provider intervention upon signs of treatment discontinuation may promote persistence.Keywords: type 2 diabetes mellitus, basal insulin, patient survey, medication persistence